Magmatic and metamorphic events during the early Paleozoic Wuyi-Yunkai orogeny, southeastern South China: New age constraints and pressure-temperature conditions - Li, Zheng-Xiang; Li, X.; Wartho, J.; Clark, Chris; Li, W.; Zhang, C.; Bao, C. (Geological Society of America, 2010)
The early Paleozoic Wuyi-Yunkai orogen in South China is a major orogenic belt in East Asia that formed at a similar time as the classic Caledonian orogeny in Europe. Despite the possibility of its being one of the few examples of intraplate orogenesis in the world, details about the orogen remain poorly defined. In this study, we provide age constraints on metamorphic and magmatic events in the eastern segment of the orogen, and the protoliths of the amphibolite-facies metamorphic rocks found there.By combining previous work with our new metamorphic and petrogenetic analyses, we present the following findings: (1) the Wuyi-Yunkai orogeny occurred between mid-Ordovician (>460 Ma) and earliest Devonian (ca. 415 Ma) time; (2) amphibolite-facies metamorphism in the eastern Wuyi-Yunkai orogen occurred between ca. 460 and 445 Ma, whereas cooling below 500–300 °C occurred by ca. 420 Ma; (3) the orogen exhibits a clockwise pressure-temperature (P-T) path and a maximum pressure of >8 kbar, indicating crustal thickening during the orogeny; (4) protoliths of the high-grade metamorphic rocks in the eastern segment of the orogen were dominantly Neoproterozoic (840–720 Ma) volcanic and volcaniclastic rift successions and younger deposits formed in a failed rift, and Paleoproterozoic rocks account for only a small proportion of the outcrops; and (5) the analyzed granites indicate a mixed source of Paleoproterozoic basement and Neoproterozoic continental rift rocks, with elevated melt temperatures of >800 °C, which are interpreted as reflecting dehydration melting of basin sediments taken to below midcrustal levels.